INVESTIGATION AND SELECTION OF OPTIMIZED CIRCUIT MODEL OF BIMORPH PIEZOELECRIC ELEMENT OF DYNAMIC PRESSURE WITH DUAL-CIRCUIT INVERSE FEEDBACK - В. В. Туз; Т. Ю. Кісіль (Вісник Черкаського державного технологічного університету, 2018)
Issues related to the selection of the optimized circuit model of a bimorph piezoelectric element of dynamic pressure with dual-circuit inverse feedback are reviewed. Characteristics of piezoelectric transducers with source charge amplifier and voltage amplifier in additional feedback path are investigated.